An etching-assisted route for fast and large-scale fabrication of non-layered palladium nanosheets. Issue 16 (11th April 2018) - Liu, Yaming; Li, Xiang; Bi, Wei; Jin, Mingshang
Abstract : A gram-scale synthesis of non-layered palladium nanosheets can be accomplished within 3 min via the etching-assisted route proposed in this study. Abstract : To date, great progress has been made in the shape-controlled synthesis of noble-metal nanocrystals. However, there still exists a major gap between academic studies and industrial applications due to the inability to produce nanocrystals in large quantities while retaining their uniformity. To help fill this gap, herein, we provide a new route to scale up and accelerate the production of non-layered palladium nanosheets (Pd NSs) by incorporating etching while retaining effective capping during the synthesis. The key to this rapid synthesis is the etching induced by selected etchants ( e.g., Fe 3+ /Fe 2+, Cl − /O2, Br − /O2, and I − /O2 ). Specifically, this synthesis can be accomplished within 3 min, reaching a yield as high as 7.2 g L −1 h −1 . The thickness of Pd NSs can be tuned to 1.6, 2.0, 2.3, and 3.5 nm by controlling the etching and reducing rates via choosing different type of etchants. Moreover, these non-layered Pd NSs are fabricated in an aqueous solution without the addition of any organic compounds; therefore, the surface of these NSs is extremely clean. When used as a catalyst for the formic acid oxidation reaction, the as-prepared non-layered Pd NSs exhibit a mass activity as high as 1350 mA mg −1, which is 3.7 times higher than that of commercial Pd/C, due to their much larger electrochemical surface area (66.2 m 2 g −1, which is 2.7 times higher than that of commercial Pd/C).